2021
DOI: 10.3389/fpsyg.2021.656776
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning in Times of COVID-19: Uses of Digital Technologies During School Lockdowns

Abstract: The closure of schools as a result of COVID-19 has been a critical global incident from which to rethink how education works in all our countries. Among the many changes generated by this crisis, all teaching became mediated by digital technologies. This paper intends to analyze the activities carried out during this time through digital technologies and the conceptions of teaching and learning that they reflect. We designed a Likert-type online questionnaire to measure the frequency of teaching activities. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
0
28

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 61 publications
10
82
0
28
Order By: Relevance
“…Thus, focusing more strongly on e-learning—as the momentarily most prominent form of learning—seems to be extremely relevant. In line with this, the COVID-19 pandemic and the resulting transfer to remote e-learning also illustrated, among others, the importance and general need for more computerized learning strategies, for more technological applications or digital technologies while learning, or for more innovative, interactive, and gamified teaching strategies to successfully adapt to the current situation and to successfully move to online teaching (see, e.g., Adedoyin and Soykan, 2020 ; Fergus, 2020 ; König et al, 2020 ; Sarju, 2020 ; Muthuprasad et al, 2021 ; Nieto-Escamez and Roldán-Tapia, 2021 ; Obrero-Gaitán et al, 2021 ; Pozo et al, 2021 ; Yu et al, 2021 ). Future work could accordingly investigate the effects of new technologies and of digital learning on education in general but specifically on the application of normally beneficial tests.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, focusing more strongly on e-learning—as the momentarily most prominent form of learning—seems to be extremely relevant. In line with this, the COVID-19 pandemic and the resulting transfer to remote e-learning also illustrated, among others, the importance and general need for more computerized learning strategies, for more technological applications or digital technologies while learning, or for more innovative, interactive, and gamified teaching strategies to successfully adapt to the current situation and to successfully move to online teaching (see, e.g., Adedoyin and Soykan, 2020 ; Fergus, 2020 ; König et al, 2020 ; Sarju, 2020 ; Muthuprasad et al, 2021 ; Nieto-Escamez and Roldán-Tapia, 2021 ; Obrero-Gaitán et al, 2021 ; Pozo et al, 2021 ; Yu et al, 2021 ). Future work could accordingly investigate the effects of new technologies and of digital learning on education in general but specifically on the application of normally beneficial tests.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety disorders are related to disrupted learning in uncertain environments [28,29]. A large-scale longitudinal epidemiologic assessment of college students in China demonstrated that mental health concerns significantly increased throughout the pandemic [30].…”
Section: Protective Factors That Can Contribute To Effective Learning In the Context Of Remote Educationmentioning
confidence: 99%
“…In a recent study [24], k-means clustering was applied to classify students according to their physiological health score, in order to study the relation between their mental health and the pandemic. Another paper classified teachers into four profiles according to their use of digital technologies during the COVID-19 lockdown [25]. Previous to the pandemic, a research used the person-centered approach to identify five student profiles in self-regulated learning [26].…”
Section: Learning Strategies and Student Profilesmentioning
confidence: 99%